Intrinsic fundamental frequency of Danish vowels - Reinholt Petersen, Niels (Annual Report of the Institute of Phonetics University of Copenhagen, 1976)
In a number of languages the intrinsic Fo of vowels has been reported to be positively correlated with tongue height. Measurements of the fundamental frequencies of Danish vowels showed a similar correlation to exist in Danish. The Fo differences between high and low vowels were greatest in long vowels in stressed position, but also short vowels in unstressed position differed with respect to intrinsic Fo, although to a much lesser degree. The hypotheses advanced to account for the intrinsic Fo differences are briefly outlined, and discussed in relation to the results of the present and other similar experiments.